Jagten på det gode citat - Om vanskelighederne ved at finde egnede ordbogseksempler i et korpus - Lorentzen, Henrik (Nordiske Studier i Leksikografi, 2001)
The paper deals with the difficulties involved in selecting good dictionary examples from a large text corpus, especially if all examples are to be taken directly from the corpus without modifications. The author gives examples of the problems that the lexicographer has to cope with when he is put face to face with authentic language, such as length, disturbing elements, difficult , errors, and lack of naturalness. Thus, the emergence of text corpora has not made the lexicographer’s work easier, but the result will hopefully be a better dictionary with better examples.